Penerapan Teknik Ecoprint Dengan Bahan Daun Dan Bunga Menjadi Produk Bernilai - Indah Rahayu Panglipur; Denok Mugi Hidayanti; Citra Cahyanti (Institut Teknologi dan Bisnis Semarang, 2024)
AL Furqon Jember Junior High School students received assistance with ecoprinting techniques. The aim is to teach students about the utilization of natural materials, encourage their creativity, and provide them with knowledge. During the Midterm Activities (MTS), this mentoring was conducted through lectures, discussions, practices, and material sharing. Students can quickly learn the ecoprint technique because the materials and tools used are easy and fast compared to batik. In addition, the materials used are readily available in the surrounding environment, namely various leaves and flowers. The result of this ecoprinting assistance is a patterned cloth that can be used as a display (decoration) and tablecloth. At the end of this assistance, the students' work was processed and utilized for display and use in the school environment.